Under the sea - Lloyd, Clare; Ward, Elle (London Dorling Kindersley, 2018)
Can you find Striped Fish and her friends hiding under the flaps? Watch out, they might jump out at you!
Hobbies
1 2
Keywords: Marine animals -- Juvenile fiction; Sea stories